Analisis Sistem Sanitasi Drainase Daerah Bantaran Sungai (Studi Kasus : Gampong Garot, Darul Imarah, Aceh Besar) - Safriza Putra; Didit Wahyudi; Irin Caisarina (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The riverbank area of Garot Village, Darul Imarah District, Aceh Besar Regency, is highly susceptible to annual flooding due to its relatively low topography, high settlement density, and inadequate drainage sanitation management. This study aims to analyze the drainage sanitation management system, identify the condition of drainage facilities and infrastructure, and formulate strategies for addressing drainage-related problems in the riverbank area of Garot Village. A qualitative approach employing thematic analysis was adopted through field observations, documentation, and interviews with village officials.